2011
DOI: 10.1002/ajmg.b.31203
|View full text |Cite
|
Sign up to set email alerts
|

Converging evidence implicates the dopamine D3 receptor gene in vulnerability to schizophrenia

Abstract: The dopamine D3 receptor has been implicated in the pathophysiology of schizophrenia (SZ). A glycine-to-serine polymorphism at codon 9 of the dopamine D3 receptor gene (DRD3), rs6280, has been widely studied for its association with SZ, but with conflicting results. Altered levels of DRD3 mRNA have also been reported in SZ compared with normal controls. Moreover, it has been suggested that DRD3 is subject to recent positive selection in European populations. To explore the potential role of DRD3 in SZ from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
(28 reference statements)
2
14
1
Order By: Relevance
“…[26][27][28] The Gly allele frequency reported herein is similar to that described in these studies, which provides further evidence supporting the hypothesis that this allele is under the influence of natural selection, being more frequent in Asian and Latin American regions. 28 Regarding the relationship between the COMT Val 158 Met polymorphism and schizophrenia, although we found a higher frequency of heterozygosity among patients, there is no consensus in the literature about this issue. A meta-analysis conducted by Glatt et al 29 indicated that the Val 158 allele might be a weak risk factor for the development of schizophrenia.…”
Section: Genotype Frequencies In Patients With Schizophrenia Versus Hsupporting
confidence: 89%
“…[26][27][28] The Gly allele frequency reported herein is similar to that described in these studies, which provides further evidence supporting the hypothesis that this allele is under the influence of natural selection, being more frequent in Asian and Latin American regions. 28 Regarding the relationship between the COMT Val 158 Met polymorphism and schizophrenia, although we found a higher frequency of heterozygosity among patients, there is no consensus in the literature about this issue. A meta-analysis conducted by Glatt et al 29 indicated that the Val 158 allele might be a weak risk factor for the development of schizophrenia.…”
Section: Genotype Frequencies In Patients With Schizophrenia Versus Hsupporting
confidence: 89%
“…It has not only been implicated in mood disorders and addiction, but personality traits [69], schizophrenia [70], [71], cognition [72], autism [73], obsessive compulsive disorder [74], and response to clozapine [75], [76] in the context of psychosis. Conceivably, the ser9gly polymorphism is capable of modulating a variety of functions and circuits in which the D3 receptor plays an integral role, perhaps explaining evidence for a recent positive selection sweep in favor of the ser9 allele in European [70] and east Asian populations [71].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased D2-like binding is observed in patients with schizophrenia after dopamine depletion, demonstrating enhanced baseline occupancy of the D2-like receptors (Abi-Dargham et al, 2000). A further association between the D3 receptor and schizophrenia is observed in genetic studies where polymorphisms of the D3 receptor have been associated with the disease (Urraca et al, 2011;Zhang et al, 2011) as well as antipsychotic efficacy (Hwang et al, 2010;Vehof et al, 2012). For this reason, there have been a number of preclinical studies suggesting that the D3-specific antagonist may represent a more specific antipsychotic profile (Gyertyán et al, 2008;Millan et al, 2008;Kiss et al, 2010).…”
mentioning
confidence: 92%